The Metaphorical Perceptions of Preparatory Program Students for "English" and "Learning English" - Hülya Pehlivan; Nilay Neyişci; Zeynep Şen Akçay (Anı Publishing, 2020)
The aim of this study is to determine the metaphorical perceptions of English Preparatory Program (EPP) students towards "English" and "Learning English". In the study group, there are 107 university students (60 female and 47 male) attending EPP in 2017-2018 academic year at Hacettepe University School of Foreign Languages. The data were collected through an open-ended questionnaire, which is expressed as "English/ learning English is like ... because...". According to the findings, participants produced 102 valid metaphors for "English" and 96 for "learning English". Metaphors were integrated into 8 conceptual categories for "English" and 10 conceptual categories for "learning English". According to the results, metaphorical perceptions of EPP students towards English are generally positive and students are aware that learning English is an inevitable necessity. The positive metaphorical perceptions of students both enrich the language and facilitate learning.